2000
DOI: 10.1021/ic000240f
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Rearrangements on the (CH)2(BR)2, RH, and NH2 Potential Energy Surfaces

Abstract: A comprehensive survey of the (CH)2(BH)2 potential energy surface was carried out at the [MP4/6-311 + G(d,p)]//MP2/6-31G(d) level. Many of the classical and nonclassical isomers of the carborane surface are separated by high activation barriers, which explains why derivatives of most isomers could be prepared as stable compounds at room temperature. The transition states are grouped into two types, hydrogen migration (terminal-to-bridge and bridge-to-terminal) and group migration (BH, CH, and CH2). The rearran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
(68 reference statements)
0
12
0
4
Order By: Relevance
“…34.58 8.Whereas the analogous reaction with adialumene precursor yields the 1,2-dihydro-1,2-dialumete IV (Figure 1), [13] the 1,3-isomer is obtained in this case.A lthough this reaction involves formal cleavage of CCa nd B=Bb onds,p revious synthetic and theoretical studies have shown that 1,2-dihydro-1,2-diboretes spontaneously rearrange to the thermodynamically more stable 1,3-isomer. [21] It is thus likely that diborene VI first undergoes the expected [2+ +2] cycloaddition to form the kinetic 1,2-dihydro-1,2-diborete,w hich immediately rearranges to the thermodynamic product, 1.T he short BÀC bond lengths to the sp 2 -hybridized C1 atom [1.486(4), 1.465-(4) ] are indicative of a2p-homoaromatic system delocalized over B1C1B2, whereas the B À Cb onds to the sp 3hybridized C3 atom [1.630(4), 1.666(4) ] are within the upper range of BÀCs ingle bonds.C ompound 1 is thus structurally similar to the allenyl-bridged 1,3-dihydro-1,3diborete reported by Berndt and co-workers. [22] TheP 1-C3 distance [1.759 (2) ] is typical for aP !Cd onor-acceptor bond;t he PMe 3 donor moiety thus stabilizes the build-up of positive charge on C3 (mesoionic resonance structure in Figure 2).…”
mentioning
confidence: 99%
“…34.58 8.Whereas the analogous reaction with adialumene precursor yields the 1,2-dihydro-1,2-dialumete IV (Figure 1), [13] the 1,3-isomer is obtained in this case.A lthough this reaction involves formal cleavage of CCa nd B=Bb onds,p revious synthetic and theoretical studies have shown that 1,2-dihydro-1,2-diboretes spontaneously rearrange to the thermodynamically more stable 1,3-isomer. [21] It is thus likely that diborene VI first undergoes the expected [2+ +2] cycloaddition to form the kinetic 1,2-dihydro-1,2-diborete,w hich immediately rearranges to the thermodynamic product, 1.T he short BÀC bond lengths to the sp 2 -hybridized C1 atom [1.486(4), 1.465-(4) ] are indicative of a2p-homoaromatic system delocalized over B1C1B2, whereas the B À Cb onds to the sp 3hybridized C3 atom [1.630(4), 1.666(4) ] are within the upper range of BÀCs ingle bonds.C ompound 1 is thus structurally similar to the allenyl-bridged 1,3-dihydro-1,3diborete reported by Berndt and co-workers. [22] TheP 1-C3 distance [1.759 (2) ] is typical for aP !Cd onor-acceptor bond;t he PMe 3 donor moiety thus stabilizes the build-up of positive charge on C3 (mesoionic resonance structure in Figure 2).…”
mentioning
confidence: 99%
“…Aus der Reihe der isoelektronischen viergliedrigen Zweielektronen‐Aromaten 1 – 3 (Schema ) sind experimentell bisher Derivate des Dikations 1 1 und des nichtgeladenen 2 24 realisiert worden. Die Barrieren ihrer Ringinversionen, die ein Maß für die Stabilisierung der gefalteten gegenüber den planaren Ringen sind, konnten experimentell in keinem Fall ermittelt werden.…”
Section: Methodsunclassified
“…[2] According to computations [3] the prototype of such molecules without metal centers is the diboracyclopropane 1 u (Scheme 1). Derivatives of the lower energy isomer 2 u with planar-tetracoordinate boron atoms [4] 16.9 kcal mol À1 . [4] For the dianion of B 4 Me 4…”
Section: Dedicated To Professor Paul Von Raguÿ Schleyermentioning
confidence: 99%
“…Derivatives of the lower energy isomer 2 u with planar-tetracoordinate boron atoms [4] 16.9 kcal mol À1 . [4] For the dianion of B 4 Me 4…”
Section: Dedicated To Professor Paul Von Raguÿ Schleyermentioning
confidence: 99%